Microstructure and Mechanical Characteristics of AlCoCrFeNi-Based ODS High-Entropy Alloys Consolidated by Vacuum Hot Pressing - Rao, K. Raja; Dewangan, Sheetal Kumar; Seikh, A. H.; Sinha, Sudip Kumar; Ahn, Byungmin (Metals and Materials International, 2024)
The study investigates that a high-entropy alloy based on AlCoCrFeNi is mechanically alloyed (MA) for 40 h with 1 wt% Y2O3 dispersed and then consolidated through vacuum hot pressing (VHP). In VHP, three temperatures are used for consolidation: 800 °C, 900 °C, and 1000 °C. Microanalysis of the powder aggregate formed by MA revealed the presence of mostly face-centered cubic (FCC) and body-centered cubic (BCC) phases, along with a metastable AlFe4O12Y3 garnet phase. The enthalpy of mixing Y and Al induced the development of the garnet phase. In addition, after the consolidation of the powder sample at different temperatures, microstructural investigations indicated that the FCC and BCC phases generated during MA were stable owing to sluggish diffusion. By contrast, the garnet phase generated during the MA dissociated into an intermetallic phase based on Yttrium. The slower heating rates associated with VHP (in comparison to the rapid heating rates associated with spark plasma sintering) may be responsible for the dissociation of the garnet phase. The sample sintered at 1000 °C exhibited a bimodal grain distribution, with grain sizes ranging from 100 to 800 nm, as determined by transmission electron microscopy. In addition, this sample had the highest measured hardness of 1353 ± 20 Hv. Graphical Abstract: (Figure presented.).
Keywords: Bimodal grain size; Bimodal grains; Body-centered-cubic phase; Face-centred cubic; Garnet phase; Grainsize; High entropy alloys; Intermetallic-phases; Mechanically alloyed; Vacuum hot pressing; Bimodal grain size; Garnet phase; High entropy alloy; Intermetallic phase; Mechanical alloying; Vacuum hot pressing